Reframing multifaceted roles of teachers through developing educational research method design: design-based classroom action research - Yundayani, Audi; Alghadari, Fiki (International Journal of Mathematics and Sciences Education, 2024)
The central concern in educational research was determining which model of a teacher's multiple roles was preferable. In the general debate on this issue, precise positions were frequently adopted. The research examined this central question and the various stances taken within the field of education. Furthermore, the study aimed to develop the design-based classroom action research as an educational research method design. Researchers synthesized qualitative research to interpret the multiple roles of teachers, which were strongly linked to their professionalism through the development of DCAR. This qualitative study gathered data through (1) focus group discussions (FGD) and (2) expert judgment. The application of the ADDIE development model—comprising analysis, design, development, implementation, and evaluation—was initiated, but the process ended during the development phase with the inclusion of an expert design evaluation. The findings from the needs analysis indicated that teacher professional development programs should focus on (1) enhancing teaching skills and knowledge, (2) improving the teacher's ability as a course designer, and (3) nurturing research skills. In response, researchers introduced DCAR as a research method design that combined the roles of course designer and classroom action researcher. Additionally, expert judgment recommended DCAR as an alternative research method design suitable for educational research. These findings highlighted the expansion of the teacher professional development model as a tool for creating a comprehensive profile of a professional teacher.